How Energy Metabolism Supports Cerebral Function: Insights from 13C Magnetic Resonance Studies In vivo - Sonnay, Sarah; Gruetter, Rolf; Duarte, João M. N. (Frontiers in Neuroscience, 2017)
Cerebral function is associated with exceptionally high metabolic activity, and requires continuous supply of oxygen and nutrients from the blood stream. Since the mid-20th century the idea that brain energy metabolism is coupled to neuronal activity has emerged, and a number of studies supported this hypothesis. Moreover, brain energy metabolism was demonstrated to be compartmentalized in neurons and astrocytes, and astrocytic glycolysis was proposed to serve the energetic demands of glutamatergic activity. Shedding light on the role of astrocytes in brain metabolism, the earlier picture of astrocytes being restricted to a scaffold-associated function in the brain is now out of date. With the development and optimization of non-invasive techniques, such as nuclear magnetic resonance spectroscopy (MRS), several groups have worked on assessing cerebral metabolism in vivo. In this context, 1H MRS has allowed the measurements of energy metabolism-related compounds, whose concentrations can vary under different brain activation states. 1H-[13C] MRS, i.e. indirect detection of signals from 13C-coupled 1H, together with infusion of 13C-enriched glucose has provided insights into the coupling between neurotransmission and glucose oxidation. Although these techniques tackle the coupling between neuronal activity and metabolism, they lack chemical specificity and fail in providing information on neuronal and glial metabolic pathways underlying those processes. Currently, the improvement of detection modalities (i.e. direct detection of 13C isotopomers), the progress in building adequate mathematical models along with the increase in magnetic field strength now available, render possible detailed compartmentalized metabolic flux characterization. In particular, direct 13C MRS offers more detailed dataset acquisitions and provide information on metabolic interactions between neurons and astrocytes, and their role in supporting neurotransmission. Here we review state-of-the-art MR methods to study brain function and metabolism in vivo, and their contribution to the current understanding of how astrocytic energy metabolism supports glutamatergic activity and cerebral function. In this context, recent data suggests that astrocytic metabolism has been underestimated. Namely, the rate of oxidative metabolism in astrocytes is about half of that in neurons, and it can increase as much as the rate of neuronal metabolism in response to somatosensory stimulation.